2016
DOI: 10.22146/agritech.16605
|View full text |Cite
|
Sign up to set email alerts
|

Ekstraksi Pektin dari Kulit dan Tandan Pisang dengan Variasi Suhu dan Metode (Pectin Extraction from Banana Peels and Bunch with Various Temperatures and Methods)

Abstract: ABSTRAKSeiring peningkatan produksi pisang tentu akan diikuti dengan peningkatan limbah pisang seperti kulit dan tandan buah pisang. Pemanfaatan limbah pisang tersebut masih belum optimal. Padahal di dalamnya terkandung substansi alami tanaman yang memiliki nilai guna tinggi yaitu pektin yang tersusun atas molekul asam galakturonat membentuk asam poligalakturonat. Pektin dimanfaatkan sebagai bahan penstabil pada sari buah, jelly, jam dan marmalade. Penelitian ini bertujuan untuk mengetahui karakteristik tepung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The organoleptic test results for banana peel pectin in terms of shape, color, and smell almost match the pectin quality standards in HOPE 2009. The resulting pectin has the same organoleptic properties as commercial pectin, which is known to have a brighter colorwhite, yellowish, gray, or brown (Nurhayati et al, 2016). Based on Table 4, the solubility test shows, when 0.1 g of pectin was dissolved in water, pectin was obtained, which dissolved in water, forming a slightly viscous liquid.…”
Section: Pectin Qualitative Test Resultsmentioning
confidence: 97%
“…The organoleptic test results for banana peel pectin in terms of shape, color, and smell almost match the pectin quality standards in HOPE 2009. The resulting pectin has the same organoleptic properties as commercial pectin, which is known to have a brighter colorwhite, yellowish, gray, or brown (Nurhayati et al, 2016). Based on Table 4, the solubility test shows, when 0.1 g of pectin was dissolved in water, pectin was obtained, which dissolved in water, forming a slightly viscous liquid.…”
Section: Pectin Qualitative Test Resultsmentioning
confidence: 97%
“…Namun, konsentrasi asam yang terlalu tinggi akan menyebabkan terjadinya degradasi pektin menjadi asam pektat, sehingga perolehan nilai total pektin akan menjadi semakin sedikit (Budiyarti et al, 2013). Sementara, pada lama waktu ekstraksi, semakin lama waktu ekstraksi, maka nilai total pektin akan meningkat karena semakin lama ekstraksi maka jaringan tanaman akan semakin lunak, sehingga protopektin yang merupakan senyawa pektin yang tidak larut dalam air yang terdapat di dalam jaringan tanaman akan semakin banyak terhidrolisis menjadi pektin yang larut dalam air (Nuh, 2017). Namun, waktu ekstraksi yang lebih lama dapat mendegradasi pektin menjadi asam pektat (Kanse et al, 2017).…”
Section: Analisa Total Pektinunclassified
“…Banana bunches are agricultural waste from banana harvests that have not been utilized properly. Banana bunch waste is often relegated to being animal feed and contributing to environmental pollution if not reused [28]. Based on previous research, banana bunches are indicated contain cellulose in the range of 35 to 51.05% [29]- [32].…”
Section: Introductionmentioning
confidence: 99%